Poverty Maps of Bangladesh 2010 : Key Findings - World Bank; World Food Programme; Bangladesh Bureau of Statistics (Washington, DC, 2014)
Poverty mapping is a statistical exercise to estimate the incidence of poverty at sub-national levels to enable the government, civil society organizations, and development partners to accurately identify locations with a relatively higher concentration of poor people. The current poverty mapping exercise was initiated in September 2012 by the Bangladesh bureau of statistics (BBS), the World Bank, and the World food program (WFP) to produce reliable poverty estimates for key subnational administrative units (zila and upazila) using data from both the 2010 household income and expenditure survey (HIES) and the 2011 population census. Poverty mapping is a powerful tool for identifying and monitoring pockets of affluence and poverty across the country. The usefulness of poverty maps can be further reinforced by combining them with other geo-referenced databases such as maps of human development indicators, maps of natural disasters, and maps of the impending impacts of climate change.